Autonomous Agriculture Robot for Monitoring Plant using Internet of Things (ELEKTRIKA- Journal of Electrical Engineering, 2022)
Agriculture robot refers to the implementation of modern technology that combines robotics and automation to overcome deficiencies of the traditional agricultural method by automating processes to dramatically increase efficiency. The robot is designed with a fully automated navigation system using line following algorithm with added features to monitor and capture the image of the plant in real-time situations. This project aims to develop a system to monitor the conditions of crops and designing a logic control for line following navigation within the boundaries of modern agriculture. The system will be realized following the process chain starting from the mapping the input from sensors to control the speed and direction of the motor. The user will be able to monitor the plant condition from the image captured through internet of things-based communication between the robot and Blynk application.